2013
DOI: 10.1016/j.jchromb.2013.06.035
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput method for the analysis of ethylenethiourea with direct injection of hydrolysed urine using online on-column extraction liquid chromatography and triple quadrupole mass spectrometry

Abstract: Ethylenethiourea (ETU) is of major toxicological concern, since in experimental animal studies, ETU has shown a large spectrum of adverse effects. High occupational exposure can be found among agricultural workers or during manufacturing of ethylenbisdithiocarbamates (EBDC). For the general public, sources of environmental exposure may be residues of ETU in commercial products, food and beverages. For the determination of ETU in human urine we present a high-throughput online on-column extraction liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The agricultural work clothes the women most often washed came from family members who worked on banana plantations. In this activity, there was a stronger association of ETU with washing the day before urine sampling compared with washing on the day of urine sampling, which may reflect relatively slow uptake of ETU after dermal exposure ( Ekman et al 2013 ). In contrast, ETU was more strongly associated with reported aerial spraying on the day of sampling than aerial spraying on the previous day, possibly due to faster absorption of mancozeb and ETU through the lungs following respiratory exposure compared with absorption via dermal exposure ( Ekman et al 2013 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The agricultural work clothes the women most often washed came from family members who worked on banana plantations. In this activity, there was a stronger association of ETU with washing the day before urine sampling compared with washing on the day of urine sampling, which may reflect relatively slow uptake of ETU after dermal exposure ( Ekman et al 2013 ). In contrast, ETU was more strongly associated with reported aerial spraying on the day of sampling than aerial spraying on the previous day, possibly due to faster absorption of mancozeb and ETU through the lungs following respiratory exposure compared with absorption via dermal exposure ( Ekman et al 2013 ).…”
Section: Discussionmentioning
confidence: 95%
“…A small occupational exposure study ( n = 13) reported associations between dermal mancozeb exposure and urinary ETU concentrations ( Colosio et al 2002 ). A recent experimental dermal exposure study on ETU in humans reported that approximately 10% of the dose of ETU applied on skin was excreted in urine ( Ekman et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specimens were aliquoted and were stored at until their shipment to Lund University, Sweden. Samples were then analyzed for ETU using a two-dimensional liquid chromatography mass spectrometer (LC-MS/MS; UFLCRX; Shimadzu Corporation) with a triple quadrupole linear ion trap (QTRAP 5500; AB Sciex) ( Ekman et al. 2013 ).…”
Section: Methodsmentioning
confidence: 99%